Search for production of a single vectorlike quark decaying to or in the all-hadronic final state in collisions at √ =13 TeV - Hayrapetyan,A; Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Hussain,PS; Jeitler,M; Krammer,N; Li,A; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2024)
A search for electroweak production of a single vectorlike T quark in association with a bottom (b) quarkin the all-hadronic decay channel is presented. This search uses proton-proton collision data at ffiffis p ¼13 TeV collected by the CMS experiment at the CERN LHC during 2016–2018, corresponding to anintegrated luminosity of 138 fb−1. The T quark is assumed to have charge 2=3 and decay to a top (t) quarkand a Higgs (H) or Z boson. Hadronic decays of the t quark and the H or Z boson are reconstructed fromthe kinematic properties of jets, including those containing b hadrons. No deviation from the standardmodel prediction is observed in the reconstructed tH and tZ invariant mass distributions. The95% confidence level upper limits on the product of the production cross section and branching fractionof a T quark produced in association with a b quark and decaying via tH or tZ range from 1260 to 68 fb forT quark masses of 600–1200 GeV.